Racial Socialization as Critical Action? Connecting Black and White Parents' Critical Consciousness to Their Anti-Racist Socialization. - Dull, Brandon D.; Rogers, Leoandra Onnie (Developmental Psychology, 2025)
Parents' critical consciousness has been theorized to facilitate race conversations that center on how social structures, policies, and historical factors perpetuate inequities, but few studies have investigated this link empirically. The current analysis examines the associations between Black and white parents' critical consciousness and their anti-racist socialization amid the 2020 Black Lives Matter movement. Participants were 725 parents (344 Black, 381 white, M = 38.08, SD = 7.00) of 8- to 11-year-old children who completed an online survey between October 2020 and January 2021, following the murder of George Floyd. Using latent profile analysis, the results show how Black and white parents' critical consciousness profiles are differentially related to whether and how they discussed Black Lives Matter with their children. Overall, both Black and white parents with higher levels of critical consciousness were more likely to engage in anti-racist socialization that countered dominant white supremacist and anti-Black ideologies, though fewer white parents did so than Black parents. The article discusses the implications of the findings for fostering critical racial socialization practices and offers a (re)conceptualization of racial socialization as a form of critical action for parents. Public Significance Statement: Parent–child conversations about race and racism have been reported to build children's skills to actively resist and challenge oppressive systems, yet we know little about how to foster such conversations. The present study examined how Black and white parents' critical consciousness (i.e., awareness of, and action against, systems of power) was associated with their racial socialization practices amid the 2020 Black Lives Matter movement. The findings emphasize how building parents' critical consciousness can serve as a pathway toward parent–child conversations that disrupt racism.